CT-definable subtypes of chronic obstructive pulmonary disease: a statement of the Fleischner society - Lynch, David A.; Austin, John H. M.; Hogg, James C.; Grenier, Philippe A.; Kauczor, Hans-Ulrich; Bankier, Alexander A.; Barr, R. Graham; Colby, Thomas V.; Galvin, Jeffrey R.; Gevenois, Pierre Alain; Coxson, Harvey O.; Hoffman, Eric A.; et al. (Radiology, 2015)
Integration of visual characterization of emphysema and airway abnormalities with physiologic and quantitative CT assessment permits categorization of chronic obstructive pulmonary disease into distinct structurally and functionally defined subtypes., The purpose of this statement is to describe and define the phenotypic abnormalities that can be identified on visual and quantitative evaluation of computed tomographic (CT) images in subjects with chronic obstructive pulmonary disease (COPD), with the goal of contributing to a personalized approach to the treatment of patients with COPD. Quantitative CT is useful for identifying and sequentially evaluating the extent of emphysematous lung destruction, changes in airway walls, and expiratory air trapping. However, visual assessment of CT scans remains important to describe patterns of altered lung structure in COPD. The classification system proposed and illustrated in this article provides a structured approach to visual and quantitative assessment of COPD. Emphysema is classified as centrilobular (subclassified as trace, mild, moderate, confluent, and advanced destructive emphysema), panlobular, and paraseptal (subclassified as mild or substantial). Additional important visual features include airway wall thickening, inflammatory small airways disease, tracheal abnormalities, interstitial lung abnormalities, pulmonary arterial enlargement, and bronchiectasis., © RSNA, 2015
Gesehen am 04.06.2020